Estrogen receptor coregulators and pioneer factors: the orchestrators of mammary gland cell fate and development - Manavathi, Bramanandam; Samanthapudi, Venkata S. K.; Gajulapalli, Vijay Narasimha Reddy (Frontiers in Cell and Developmental Biology, 2014)
The steroid hormone, 17β-estradiol (E2), plays critical role in various cellular processes such as cell proliferation, differentiation, migration and apoptosis, and is essential for reproduction and mammary gland development. E2 actions are mediated by two classical nuclear hormone receptors, estrogen receptor α and β (ERs). The activity of ERs depends on the coordinated activity of ligand binding, post-translational modifications (PTMs), and importantly the interaction with their partner proteins called “coregulators.” Because coregulators are proved to be crucial for ER transcriptional activity, and majority of breast cancers are ERα positive, an increased interest in the field has led to the identification of a large number of coregulators. In the last decade, gene knockout studies using mouse models provided impetus to our further understanding of the role of these coregulators in mammary gland development. Several coregulators appear to be critical for terminal end bud (TEB) formation, ductal branching and alveologenesis during mammary gland development. The emerging studies support that, coregulators along with the other ER partner proteins called “pioneer factors” together contribute significantly to E2 signaling and mammary cell fate. This review discusses emerging themes in coregulator and pioneer factor mediated action on ER functions, in particular their role in mammary gland cell fate and development.